Mitigating climate risks in coffee production through agroforestry: global evidence from a systematic review and meta-analysis - Patil, Somashekhargouda; Rudragouda, C. S.; Govindappa, M.; Roobakkumar, Amsalingam; Machenahalli, Santoshreddy; Jingade, Pavankumar; Nadaf, S. A.; Mote, Kishor; Uma, M. S.; Tintumol, K.; Yashasvi, H. R.; Yashaswini, K. P.; et al. (Frontiers in Climate, 2025)
BackgroundClimate change presents mounting challenges to coffee systems globally, driving the search for resilient agricultural strategies. Agroforestry has emerged as a promising climate adaptation approach, yet its effectiveness across diverse outcomes and contexts remains uncertain.ObjectiveTo systematically review scientific literature on (i) Climate change impacts on coffee production and (ii) Effectiveness of agroforestry-based adaptation and mitigation strategies using qualitative synthesis and meta-analysis for sustainable coffee cultivation.MethodsConducted a comprehensive search across 13 databases, screening 3,357 records. Sixty-eight studies (2000–2024) met inclusion criteria, assessing agroforestry impacts under climate-related stressors. Data extraction followed PRISMA 2020 guidelines. A random-effects meta-analysis was conducted on 68 effect sizes categorized into pest/disease incidence, yield loss and quality degradation. Heterogeneity, bias and publication quality were assessed using ROBINS-I and GRADE-CERQual criteria.ResultsAgroforestry interventions reduced climate-related yield loss (OR = 0.67 [0.56–0.80], I2 = 0%), pest and disease incidence (OR = 0.79 [0.67–0.95], I2 = 0%) and quality degradation (OR = 0.74 [0.63–0.86], I2 = 0%). The homogeneity across subgroups suggests consistent benefits across agroecological zones. However, most studies lacked PROSPERO registration and conceptual framing.ConclusionAgroforestry enhances adaptive capacity and farm resilience in coffee systems under climate stress. These effects are consistent across yield, pest and quality outcomes. To support theory-building, future studies should integrate resilience frameworks and improve methodological transparency. Findings provide actionable insights for climate-resilient coffee farming.